Fear of COVID-19 among homeless individuals in Germany in mid-2021 - Hajek, André; Bertram, Franziska; Rüth, Victoria van; Dost, Katharina; Graf, Wiebke; Brenneke, Anna; Kowalski, Veronika; Püschel, Klaus; Schüler, Christine; Ondruschka, Benjamin; Heinrich, Fabian; König, Hans-Helmut (Frontiers in Public Health, 2022)
Aims: To investigate the prevalence and the correlates of fear of COVID-19 among homeless individuals. Methods: We used data from the “national survey on psychiatric and somatic health of homeless individuals during the COVID-19 pandemic” (NAPSHI-study) which took place in several large cities in Germany in Mid-2021 (n=666 in the analytical sample). Mean age equaled 43.3 years (SD: 12.1 years), ranging from 18 to 80 years. Multiple linear regressions were performed. Results: In our study, 70.9% of the homeless individuals reported no fear of COVID-19. Furthermore, 14.0% reported a little fear of COVID-19, 8.4% reported some fear of COVID-19 and 6.7% reported severe fear of COVID-19. Multiple linear regressions revealed that fear of COVID-19 was higher among individuals aged 50 to 64 years (compared to individuals aged 18 to 29 years: β=.28, p<.05), among individuals with a higher perceived own risk of contracting the coronavirus one day (β=.28, p<.001) as well as among individuals with a higher agreement that a diagnosis of the coronavirus would ruin his/her life (β=.15, p<.001). Conclusions: Only a small proportion of homeless individuals reported fear of COVID-19 in mid-2021 in Germany. Such knowledge about the correlates of higher levels of fear of COVID-19 may be helpful for addressing certain risk groups (e.g., homeless individuals aged 50 to 64 years). In a further step, avoiding extraordinarily high levels of fear of COVID-19 may be beneficial to avoid irrational thinking and acting regarding COVID-19 in this group.